Pharmacist-led educational intervention to improve knowledge, medication adherence, and asthma control among asthma patients at Ayder Comprehensive Specialized Hospital: A protocol for randomized controlled trial - Mekuriaw Dereje Tekele; Goitom Belay Kassa; Yainu Welegerima Welekidane; Derbew Fikadu Berhe; Abadi Kahsu Gebre; Afewerki Gebremeskel Tsadik (PLoS ONE, 2026)
Objective To evaluate the effect of a pharmacist‑led educational intervention on medication knowledge, adherence, and asthma control among adult asthma patients at Ayder Comprehensive Specialized Hospital, Ethiopia. Methods A single‑blind, parallel‑group randomized controlled trial will be conducted. All eligible adult asthma patients on active follow‑up at the chest clinic of Ayder Comprehensive Specialized Hospital will be included. Participants will be randomly assigned via a computer‑generated sequence to an intervention group (structured pharmacist‑led education using teach‑back, illustrated pamphlets, a follow‑up phone call and SMS) or a control group (routine care). Outcome assessors will be blinded to group allocation. Outcomes will be measured at baseline and after three months, including medication adherence (GMAS), asthma control (ACT), medication knowledge, correct inhaler technique, and domain‑specific adherence barriers. Data will be analyzed using intention‑to‑treat with multivariable binary logistic regression, chi‑square tests, independent T-test, McNemar test, Mann‑Whitney U test, and Fisher’s exact test where appropriate. Subgroup analyses will be performed to explore whether the intervention effect differs across patient characteristics. A p‑value < 0.05 will be considered statistically significant, with 95% confidence intervals reported. Trial registry Pan African Clinical Trials Registry (PACTR202508565637179).